2017
DOI: 10.1177/1541931213601694
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Users’ Experience of Face Blurring as a Privacy Protection for Sharing Photos via Online Social Networks

Abstract: Photo sharing on online social networks (OSNs) can cause privacy issues. Face blurring is one strategy to increase privacy while still allowing users to share photos. To explore the potential blurring has as a privacy-enhancing technology for OSN photos, we conducted an online experiment with 47 participants to evaluate the effectiveness of face blurring compared to the original photo (as-is), and users’ experience (satisfaction, information sufficiency, enjoyment, social presence, and filter likeability). Use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
0
16
2
Order By: Relevance
“…It also performed reasonably well in our more extensive testing in Chapters 5 and 6. Other research suggests that representations such as pixelation or blurring are actually ineffective at preserving privacy of social media photos [78]. In Chapter 4, we found that the pixelation representations were interpreted as "concealing"; they invoked negative connotations and aroused suspicion.…”
Section: R1: Have Digital Decay Features Enabled By Default As a Failmentioning
confidence: 73%
See 4 more Smart Citations
“…It also performed reasonably well in our more extensive testing in Chapters 5 and 6. Other research suggests that representations such as pixelation or blurring are actually ineffective at preserving privacy of social media photos [78]. In Chapter 4, we found that the pixelation representations were interpreted as "concealing"; they invoked negative connotations and aroused suspicion.…”
Section: R1: Have Digital Decay Features Enabled By Default As a Failmentioning
confidence: 73%
“…One approach is to fully or partially obfuscate sensitive imagery (photo/video) elements [55,61,78,105] or user attributes [25,115,117]. Obfuscating attributes, however, may not be effective against inference 4 attacks [25].…”
Section: Obfuscationmentioning
confidence: 99%
See 3 more Smart Citations